2020
DOI: 10.1186/s12889-020-8167-1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites among food handlers of food service establishments in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Intestinal parasites remain considerable public health problems in low-income countries where poor food hygiene practice is common. Food handlers, people involved in preparing and serving food, working with poor personal hygiene could pose a potential threat of spreading intestinal parasites to the public in a community. The aim of this systematic review and meta-analysis was, therefore, to synthesize the pooled prevalence estimate of intestinal parasites and associated pooled odds ratio of hygieni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…In study of Adane et al, 2018;Yesigat et al, 2020;and Yimam et al, 2020; revealed 96%, 57% and 54% prevalence of hand washing among food handlers after using toilet [23] [26] [25]; whereas in our study, it was 56.98%. Thus our study results were consistent with previous international studies of Yesigat et al, 2020;and Yimam et al, 2020;[23] [26]; and less as compared to Adane et al, 2018 [25]. Moreover, in our study, 35.09% frequency was revealed for washing hands before handling food items and was supported by international studies of…”
Section: Practices Of Foodcontrasting
confidence: 65%
“…In study of Adane et al, 2018;Yesigat et al, 2020;and Yimam et al, 2020; revealed 96%, 57% and 54% prevalence of hand washing among food handlers after using toilet [23] [26] [25]; whereas in our study, it was 56.98%. Thus our study results were consistent with previous international studies of Yesigat et al, 2020;and Yimam et al, 2020;[23] [26]; and less as compared to Adane et al, 2018 [25]. Moreover, in our study, 35.09% frequency was revealed for washing hands before handling food items and was supported by international studies of…”
Section: Practices Of Foodcontrasting
confidence: 65%
“…lumbricoides were reported as the predominant intestinal parasite despite variation in the reported magnitude [ 54 , 56 ]. Our finding also in agreement with systematic review and meta-analysis which pointed out these two parasites as common causes of intestinal infection [ 58 ]. Moving to the helminthic infections it was reported that Ascaris lumbricoides was the most common helminth followed by Hookworms (Ancylostoma duodenale/Necator americanus , Hymenolepis nana and T .…”
Section: Discussionsupporting
confidence: 93%
“…The combined analysis of eligible studies was assessed by the Z test based on a fixed ( P h > 0.1) or random ( P h < 0.1) model. Publication bias within the included studies was evaluated by funnel plots ( 17 ). The Stata v.11.0 software (Stata Corporation, College Station, TX, USA) was used for all statistical analyses, and p < 0.05 was considered to indicate statistical significance.…”
Section: Methodsmentioning
confidence: 99%